Sinkretisme dan Nilai dalam Tradisi Nyadran di Desa Mojodadi : Syncretism and Values in the Nyadran Tradition in Mojodadi Village - Fernanda Maulana; Haerussaleh Haerussaleh; Afan Faizin (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
The Nyadran tradition is one of the Javanese cultural rituals that is still maintained as part of social and religious life. In Mojodadi Village, Kedungpring District, Lamongan Regency, the Nyadran tradition is unique for blending Hindu-Javanese elements with Islamic teachings. This phenomenon indicates the practice of cultural syncretism that not only survives but also adapts to the belief system of modern society. This study aims to describe the form of syncretism and reveal the values ??contained in the implementation of the Nyadran Tradition in Mojodadi Village. This study uses a qualitative, descriptive method. Data collection techniques include direct observation during the implementation of the Nyadran ritual, in-depth interviews with caretakers, religious leaders, village officials, and community supporters of the tradition, and documentation in the form of photos, videos, and recordings of ritual speech. Data analysis is carried out through the stages of data reduction, data presentation, and systematic conclusion drawing. The results of the study indicate that syncretism in the Nyadran Tradition is apparent in three main dimensions, namely the verbal dimension characterized by the combination of Javanese ujub and mantras with the recitation of Yasin, tahlil, and Islamic prayers; the material dimension seen in the use of ambeng, flowers, and offerings that are reinterpreted as a form of charity; and the spatial-temporal dimension reflected in the choice of the lake as the location of the ritual and the month of Maulud as the time of implementation. In addition, the Nyadran Tradition contains religious-spiritual, social-collective, and moral-ethical values ??that strengthen the community's cultural identity. Thus, the Nyadran Tradition serves as a bridge between ancestral cultural heritage and Islamic teachings, and it plays a social, spiritual, and educational role for the people of Mojodadi Village.